Xanthohumol-induced transient superoxide anion radical formation triggers cancer cells into apoptosis via a mitochondria-mediated mechanism - Strathmann, Julia; Klimo, Karin; Sauer, Sven; Okun, Jürgen G.; Prehn, Jochen H. M.; Gerhäuser, Clarissa (The FASEB journal, 2010)
ABSTRACTOxidative stress and increased release of reactive oxygen species (ROS) are associated with apoptosis induction. Here we report ROS-mediated induction of apoptosis by xanthohumol (XN) from hops. XN at concentrations of 1.6-25 µM induced an immediate and transient increase in superoxide anion radical (O2−·) formation in 3 human cancer cell lines (average ±sd EC50 of maximum O2−· induction=3.1 ±0.8 µM), murine macrophages (EC50=4.0±0.3 µM), and BPH-1 benign prostate hyperplasia cells (EC50=4.3±0.1 µM), as evidenced by the O2−· -specific indicator dihydroethidium. MitoSOX Red costaining and experiments using isolated mouse liver mitochondria (EC50=11.4±1.8 µM) confirmed mitochondria as the site of intracellular O2−· formation. Antimycin A served as positive control (EC50=12.4±0.9 µM). XN-mediated O2−· release was significantly reduced in BPH-1 ρ0 cells harboring nonfunctional mitochondria (EC50>25 µM) and by treatment of BPH-1 cells with vitamin C, N-acetylcysteine (NAC), or the superoxide dismutase mimetic MnTMPyP. In addition, we demonstrated a rapid 15% increase in oxidized glutathione and a dose-dependent overall thiol depletion within 6 h (IC50 = 24.3±11 µM). Respiratory chain complexes I-III were weakly inhibited by XN in bovine heart submitochondrial particles, but electron flux from complex I and II to complex III was significantly inhibited in BPH-1 cells, with IC50 values of 28.1 ± 2.4 and 24.4 ± 5.2 µM, respectively. Within 15 min, intracellular ATP levels were significantly reduced by XN at 12.5 to 50 µM concentrations (IC50 = 26.7 ±3.7 µM). Concomitantly, XN treatment caused a rapid breakdown of the mitochondrial membrane potential and the release of cytochrome c, leading to apoptosis induction. Pre- or coincubation with 2 mM NAC and 50 µM MnTMPyP at various steps increased XN-mediated IC50 values for cytotoxicity in BPH-1 cells from 6.7 ± 0.2 to 12.2 ± 0.1 and 41.4 ± 7.6 µM, and it confirmed XN-induced O2−· as an essential trigger for apoptosis induction. In summary, we have identified mitochondria as a novel cellular target of XN action, resulting in increased O2−· production, disruption of cellular redox balance and mitochondrial integrity, and subsequent apoptosis.—Strathmann, J., Klimo, K., Sauer, S. W., Okun, J. G., Prehn, J. H. M., Gerhäuser, C. Xanthohumol-induced transient superoxide anion radical formation triggers cancer cells into apoptosis via a mitochondria-mediated mechanism. FASEB J. 24, 2938-2950 (2010). www.fasebj.org